PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEDA TUGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD STATE 181 PEKANBARU - Amir Mahmud; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to improve learning outcomes IPA fourth grade students of SD State 181 Pekanbaru through cooperative learning model type Number Head Together (NHT). The subjects were fourth grade students of SD State 181 Pekanbaru academic year 2014/2015 the number of students as many as 38 people. While the object of this research is to improve student learning outcomes through cooperative learning model type Number Head Together (NHT) .Penelitian was conducted in two cycles, the first cycle consists of two meetings with one repetition end of the cycle and the second cycle also consists of two cycle consists of two meetings with one repetition end of the cycle. Instruments of data collection in this study is the observation sheet teacher and student observation sheets and sheets of research results. The level of students' abilities before action categorized as low to the average value of 67. While the value of the minimum completeness criteria 70. Among the students numbering 38 people only 15 people who reached the KKM with a percentage value of 39.47%. In the first UAS student learning rose by an average of 72.39 with both categories. While student learning outcomes after action UAS II with an average value of 83.47 categorized as very good. Instruments of data collection using observation sheets and sheets teacher observation of students during the learning process takes place in class IV SD State 181 Pekanbaru, activities percentage of teachers in the first cycle of the first meeting of 55.55% with enough categories, at the second meeting of the first cycle of 69.44% considered good. Furthermore, the percentage of second cycle of the first meeting 80.55% categorized as good, at the second meeting of the second cycle 94.44% categorized as very good. Furthermore, the activity of the first cycle students first meeting of the percentage of 44.44% is categorized less, the second meeting of the first cycle of 61.11% considered good. Furthermore, the second cycle of the first meeting of 77.77% categorized either at the second meeting of the second cycle 91.67% categorized as very good. From the above explanation shows that through a cooperative learning model type Number Head Together (NHT). IPA can improve learning outcomes fourth grade students of SD State 181 Pekanbaru.Keywords: Cooperative Learning Model Type Number Head Together (NHT), IPA Learning Outcomes